The phylogeny of basal archosaurs - Juul, Lars (Bernard Price Institute for Palaeontological Research, 1994)
Archosaur systematics has received much attention from the mid 1970s and several influential works on this topic have emerged. As discrepancy exists among proposed phylogenies, some of the most important of the papers in question are assessed here. Characters used in cladistic analysis have often been selected too uncritically or phrased too vaguely to be of diagnostic value, and previously used, seemingly valid apomorphies have been disregarded by later workers, sometimes for no apparent reason. In the present paper a character matrix for the Archosauria was assembled by critically incorporating, and often modifying, characters used in earlier works on archosaur systematics. A phylogeny resulting from cladistic analysis of the matrix compiled here supports the monophyly of Archosauria, Crown-group Archosauria Crurotarsi, Ornithodira, Dinosauromorpha and Dinosauria, and disputes the existence of Suchia less Ornithosuchidae and of a monophyletic Crocodylotarsi. A new taxon, Dromaeosuchia, is erected for a clade consisting of Ornithosuchidae, Crocodylomorpha and Gracilisuchus plus Postosuchus.
Keywords: phylogeny; archosaurs; assessment